2005
DOI: 10.1063/1.1925273
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic potential switching algorithm for Monte Carlo simulations of complex systems

Abstract: This paper describes a new Monte Carlo method based on a novel stochastic potential switching algorithm. This algorithm enables the equilibrium properties of a system with potential V to be computed using a Monte Carlo simulation for a system with a possibly less complex stochastically altered potentialṼ . By proper choices of the stochastic switching and transition probabilities, it is shown that detailed balance can be strictly maintained with respect to the original potential V . The validity of the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…15,16) We hereafter consider a lattice system with pairwise long-range interactions described by the Hamiltonian…”
Section: Stochastic Cutoff (Sco) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16) We hereafter consider a lattice system with pairwise long-range interactions described by the Hamiltonian…”
Section: Stochastic Cutoff (Sco) Methodsmentioning
confidence: 99%
“…15,16) To our knowledge, this is the first method for general long-range interacting systems that greatly reduces computational time without any approximation. This method is applicable to any lattice system with long-range interactions.…”
Section: Conclusion Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, [14] have shown that the algorithm's performance depends on the tightness of the bound; it only achieves significant gains when computational light and tight bounds are applicable. The idea of using lower bounds to reduce the cost of MCMC has been exploited previously in [24]; [11] (Section 4.3) propose construction of the lower bound that avoids specifying a resampling fraction, but it requires the integrals of the exponents of the lower bound functions to be tractable.…”
Section: Custom-precision Firefly Mcmc (Cf-mcmc)mentioning
confidence: 99%
“…13,14) The switching probability to 0 and that toV ij are P ij and 1 − P ij , respectively. Since the pseudointeractionV ij and switching probability P ij are chosen properly in the SPS algorithm, the SCO method strictly satisfies the detailed balance condition concerning the original Hamiltonian.…”
Section: )mentioning
confidence: 99%